Pengembangan Aplikasi Sastra Lisan (Lawas) Khas Sumbawa Berbasis Android - Ilmiah, Zaddwi Jiwa; Esabella, Shinta (Buletin Ilmiah Informatika Teknologi, 2024)
Oral Literature (Lawas) or more commonly referred to as folk poetry, is an expression that continues to grow among the people of Sumbawa to this day. It is used as a means to express feelings to someone, either individually or in groups. This research aims to develop an Android-based Sumbawa Typical Oral Literature Application that aims to produce a more attractive appearance with additional audio and video features in the delivery of old. The data collection methods used are interview methods and literature studies. This application was built using the waterfall software development method, with Unifield Modeling Language (UML) modeling, laravel framework and dart language flutter and black box testing. The results of this study are old oral literature applications with a web system for admins and android for users. It is hoped that the development of this application can help maintain and disseminate the old poetry tradition of the Sumbawa region and help the field of Sumbawa district cultural services in preserving Sumbawa culture.